RERATA PULSATILITY INDEX ARTERI SEREBRI MEDIA PADA PENYANDANG DIABETES MELLITUS DENGAN ATAU TANPA RETINOPATI - Uly Indrasari, Salim Harris, Dante Saksono H, Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION CEREBRAL MICROANGIOPATHY IS ONE OF THE MOST IMPORTANT COMPLICATIONS IN DIABETES MELLITUS ELEVATION IN PULSATILITY INDEX PI MEASURED BY TRANSCRANIAL DOPPLER TCD HAS BEEN POSTULATED TO REFLECT INCREASEDVASCULAR RESISTANCE DISTAL TO THE ARTERY BEING EXAMINED DIABETIC PATIENTS WITH RETINAL MICROANGIOPATHY USUALLY HAVE CEREBRAL MICROANGIOPATHY ALSO TCD EXAMINATION IS RELATIVELY SAFE AND CHEAPER COMPARES WITH IMAGING TO DETECT THE COMPLICATION IN CEREBRAL ARTERY IN PATIENTS WITH DIABETIC